PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN KOLAM RENANG D'MARMAID - Khoirunnisa, Ratu; Redyan Tasip, Tamam Adiyansah; Soaduon Hasibuan, Salim Amani; Sanjaya, Vicky F (Journal for Management Student (JFMS), 2023)
This research aims to explore the impact of price and service quality on customer satisfaction at the D'Mermaid Tirtayasa Swimming Pool. By carrying out this analysis, it is hoped that variables that have an important role in shaping customer satisfaction can be investigated, including aspects of price and level of service quality. The research method applied is a quantitative approach with data collection techniques using questionnaires. It is hoped that the findings from this research can provide a significant contribution in understanding and increasing the level of customer satisfaction within the D'Mermaid Tirtayasa Swimming Pool environment. Keywords: Price, Service quality, customer satsfaction